Black-Box Testing Using the State Transition Technique on the Web-Based Clinic Appointment System “Citra Medica” (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
Software testing is an essential stage to ensure the quality and reliability of a system before it is widely deployed. One of the commonly used methods is black box testing, which focuses on evaluating the functionality of the software without considering the internal structure of the code. In this study, the black box testing method was applied using the state transition technique to test the web-based clinic appointment system “Citra Medica.” The testing process involved mapping user state flows through a transition diagram and creating test scenarios for each state change. The test results showed that all system functions operated according to the specifications, with a 100% success rate achieved in every transition scenario. This method proved effective in detecting logical errors and ensuring system stability during user state transitions